2012
DOI: 10.19173/irrodl.v13i2.1137
|View full text |Cite
|
Sign up to set email alerts
|

Examining the reuse of open textbooks

Abstract: <p>An important element of open educational resources (OER) is the permission to use the materials in new ways, including revising and remixing them. Prior research has shown that the revision and remix rates for OER are relatively low. In this study we examined the extent to which the openly licensed Flat World Knowledge textbooks were being revised and remixed. We found that the levels of revision and remix were similar to those of other OER collections. We discuss the possible significance and implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
13
2
1
Order By: Relevance
“…However, a preference to Revise and Remix learning materials rather than Reuse them was identified. This finding is significantly different than the findings of former studies (Hilton et al, 2012), although it is important to emphasize that the majority of literature deals with general OER usage and did not focus on internal repositories. Still, this finding indicates the preferences of corporate instructional designers; and although internal repositories might contain items that can be useful just as they are, corporate instructional designers often choose to alter them.…”
Section: The Usage Of Internal Repositoriescontrasting
confidence: 99%
See 4 more Smart Citations
“…However, a preference to Revise and Remix learning materials rather than Reuse them was identified. This finding is significantly different than the findings of former studies (Hilton et al, 2012), although it is important to emphasize that the majority of literature deals with general OER usage and did not focus on internal repositories. Still, this finding indicates the preferences of corporate instructional designers; and although internal repositories might contain items that can be useful just as they are, corporate instructional designers often choose to alter them.…”
Section: The Usage Of Internal Repositoriescontrasting
confidence: 99%
“…While the literature suggests high rates of Reuse and low rates of Revise and Remix usage (Hilton et al, 2012), the current study found high rates of Revise and Remix use of pictures, videos, and Wikipedia. This finding supports the second hypothesis that Revise and Remix use is more frequent among instructional designers than the literature reports.…”
Section: The Usage Of Little External Repositoriescontrasting
confidence: 79%
See 3 more Smart Citations